YOUTH CORPORATE SUBCULTURE AS A CONDITION FOR THE IMPLEMENTATION OF THE POTENTIAL OF YOUNG EMPLOYEES OF THE COMPANY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article is devoted to the youth corporate subculture as a condition for realizing the potential of young employees of the company. The article discusses that corporate subculture can become a source and condition for generating great value for the company, but this requires special attention from the head.